Dialysis Catheter Placement via the Left Internal Jugular Vein: Risk of Brachiocephalic Vein Perforation. Issue 4 (July 2016) - Winkes, Michiel B.; Loos, Maarten J.; Scheltinga, Marc R.; Teijink, Joep A.
Purpose: We discuss a case of a brachiocephalic vein (BCV) perforation after Tesio ® central venous catheter insertion. Method and Results: An 80-year-old patient underwent an ultrasound-guided hemodialysis (HD) catheter placement via his left internal jugular vein (IJV). One day postoperatively, the patient became hemodynamically unstable immediately after HD initiation. As a vascular event was feared, an emergency CT scan was performed demonstrating a BCV perforation. The patient underwent a sternotomy, the lines were removed and the venous laceration was closed. The patient recovered well. Conclusions: In spite of ultrasound guidance, fluoroscopy for guidewire and sheath advancement, venous blood aspiration and a normal appearing postoperative x-ray, traumatic central venous catheter placement is still possible. Tenting of the BCV wall during catheter advancement possibly caused the venous perforation. A 'how-to' for correct catheter placement via the IJV is provided and potential pitfalls during each procedural step are discussed.